Quantum well engineering in InGaN/GaN core-shell nanorod structures. (27th September 2017) - Bryce, C G; Le Boulbar, E D; Coulon, P-M; Edwards, P R; Gîrgel, I; Allsopp, D W E; Shields, P A; Martin, R W
Abstract: We report the ability to control relative InN incorporation in InGaN/GaN quantum wells (QWs) grown on the semi-polar and non-polar facets of a core-shell nanorod LED structure by varying the growth conditions. A study of the cathodoluminescence emitted from series of structures with different growth temperatures and pressures for the InGaN QW layer revealed that increasing the growth pressure had the effect of increasing InN incorporation on the semi-polar facets, while increasing the growth temperature improves the uniformity of light emission from the QWs on the non-polar facets.